Factors that enable and constrain the internationalisation and Africanisation of Master of Public Health programmes in South African highereducation institutions - J Witthuhn; C le Roux (South African Medical Association, 2017)
Background. Higher education worldwide is currently shaped by globalisation and internationalisation, while African and South African (SA) highereducation institutions (HEIs) are required to Africanise their curricula to equip students to become effective and responsive global citizens, with globally and locally relevant knowledge and skills.Objectives. To establish the extent to which curricula for Master of Public Health programmes (MPHPs) within schools of public health or faculties of health sciences in selected HEIs in SA are currently internationalised and Africanised.Methods. The study followed a multiple-case-study design. Semi-structured and focus-group interviews with course co-ordinators, lecturers and students provided data. The study was conducted at three HEIs in SA that offer an MPHP. Tesch’s interactive process of qualitative data coding and analysis was used.Results. According to academics, there is no clear understanding or working definition of concepts and processes such as internationalisation and Africanisation as they apply to their professional contexts. The institutions do not subscribe to policies regarding internationalisation and Africanisation either. Academics are uncertain whether curricula meet the requirements of internationalisation and Africanisation, while students consider the curricula to be internationalised and Africanised to the best of their institutions’ and lecturers’ abilities.Conclusion. There is an urgent need for curriculum transformation in SA, to ensure that the internationalisation and Africanisation of curricula occur. Curriculum transformation and the formalisation of the processes of internationalisation and Africanisation through policy changes and capacity building need to be forefronted.